Simulating traffic flow for emergency evacuation in Manhattan, KS using Rockwell ARENA - Davis, Kathryn (Kansas State University, 2010)
The community of Manhattan, Kansas was recently chosen as the future site of the National Bio- and Agro-Defense Facility (NBAF). At this site, research of agricultural and animal diseases and pathogens will take place. Due to the fact that the site will be in close proximity to a university, as well as many residents, a risk assessment must be completed to determine whether or not the current road infrastructure would be sufficient for evacuating the city in the event of an emergency. It should be noted that while NBAF is a large concern for this report, risk management is important in other scenarios as well, such as natural disasters or chemical spills, and this information can be applied to such events. This paper discusses the creation and analysis of a discrete-event simulation using ARENA software. The simulation described several scenarios. They were a base case scenario with only campus traffic evacuating; a scenario in which campus and outside traffic evacuate; a case with increased outside traffic; a case in which a vehicle breaks down; a case which includes guardians of children attending campus childcare are re-routed to pick up their children before evacuating; a case which accounts for reduced traveling speeds due to cell phone usage; and a case which closes a direction outside of Manhattan due to wind direction. Such simulations are an ideal performance measure of traffic flow under certain conditions due to the fact that physical resources are not needed to make a realistic comparison between each of them. Each of the situations described above were compared based on percentage of traffic leaving Manhattan and arriving at a defined safe zone each hour. Based on the findings, those involved with disaster management planning can determine if the percentages of vehicles leaving the system per hour are acceptable. They should be evaluated against potential spread rates of diseases to ensure that all residents may evacuate without the danger of becoming infected. For applications outside of NBAF, the results give insight into the degree of change in evacuation percentage that changes within the system may cause, and change any routing accordingly.
Keywords: simulation; emergency evacuation; Engineering, Industrial (0546); Transportation (0709)